Startups de energia : identificando os padrões vencedores durante a transição energética - Mendonça, Hudson Lima (2018)
Similarly to what happened to the communications sector during the internet revolution, startups may have a pivotal role in the energy sector during the current energy transition to a low-carbon economy. The particularities of energy startups, however, mean that the growth model based on venture capital investments, which leveraged digital startups of the beginning of the 21st century, may not work equally well for clean energy startups. Thus, this article aims to identify the patterns associated with the success of energy startups in the last 20 years and develop a predictive model utilizing logistic regression. Results show that there are, in fact, some identifiable standards among the winners, such as the volume of resources previously received and their foundation date. However, being linked to sustainability or having received corporate or angel investments were not found to be determining factors for the success of energy startups in the period.